Comparative In Vitro Analysis of Propolis and 3% Hydrogen Peroxide as Cerumenolytic Agents in Children - Ritonga, Doli Naufal; Nasution, Muhammad Edy Syahputra (Universitas Muhammadiyah Sumatera Utara, 2027)
Abstract: Cerumen impaction is a common otologic problem that can impair hearing and predispose individuals to external ear infections. This in vitro study aimed to compare the cerumenolytic effects of propolis and 3% hydrogen peroxide using spectrophotometric absorbance measurements at 5, 10, 15, and 30 minutes. A total of 48 cerumen samples were collected from children at Panti Asuhan Putri Aisyiyah Medan and divided equally into two treatment groups. Absorbance values were analyzed using non-parametric statistical tests due to non-normal data distribution. Propolis demonstrated a progressive increase in absorbance over time, reaching its highest effect at 30 minutes, whereas hydrogen peroxide showed minimal changes with no significant time-dependent pattern. Comparative analysis revealed that propolis produced significantly higher absorbance values than hydrogen peroxide at all time points (p 0.001), indicating superior cerumen dissolution. These findings suggest that propolis may serve as a more effective and potentially safer alternative to hydrogen peroxide for cerumen management. Further in vivo and clinical studies are recommended to validate its therapeutic applicability and long-term safety.